EDUKASI ABDOMINAL STRETCHING UNTUK PENURUNAN NYERI DYSMENORRHEA PADA REMAJA PUTRI - Andriani, Dewi; Sulistyana, Caturia Sasti; Fardiana, Mirza; Gading, Widyas; Rameswari, Yuniar (Community Development in Health Journal, 2023)
Introduction & Aim : Dysmenorrhea is a symptomatic phenomenon during menstruation in some women. Dysmenorrhea occurs due to excessive release of prostaglandins so that uterine contractions increase. Dysmenorrhea is pain that is felt during menstruation (menstruation) which can interfere with the activities and productivity of adolescents. Efforts that can be done include doing abdominal stretching physical activities. The purpose of this community service activity is to provide education regarding the effectiveness of abdominal stretching to reduce Dysmenorrhea pain in young women. Method of Implementation: The community service will be held from November-December 2022 using a demonstration of the Abdominal Stretching technique which has previously been given counseling beforehand. The participants as the target were young women who experienced menstrual pain at the Gembong Sawah Tengah Girls Dormitory Gang 1, Kapasan, Simokerto District, with a total of 20 participants. The measuring instrument used was the Visual Analouge Scale (VAS). Results: Most of the participants were aged 19-21 years (71%), experienced menarche at the age of 11-15 years (100%), and had menstrual cycles of 28-31 days (100%). Based on the data before doing Abdominal Stretching, most of them experienced dysmenorrhea with moderate pain levels (65%) and severe pain (25%). The results of activities after doing Abdominal Stretching procedures, pain levels were in the moderate category (30%) and no one experienced severe pain. Discussion : Abdominal stretching exercises can maintain and develop flexibility in the abdominal area and increase the release of endorphins which function as natural sedatives that can increase comfort and reduce pain.